A new distribution record of Albunea groeningi (Crustacea: Anomura: Decapoda: Albuneidae) from the Digha Coast, West Bengal, India - Kumar, J. S. Yogesh; Boyko, Christopher B.; Arun, G.; Geetha, S.; Raghunathan, C. (Zootaxa, 2020)
Members of the genus Albunea Weber, 1795 (family Albuneidae) are commonly known as sand crabs. Albuneidae contains 59 species belonging to 13 genera (Boyko & McLaughlin 2010; WoRMS 2019), of which four genera and nine species are known only as fossils. Most species are relatively uncommon and adapted to living in sandy habitats (Boyko & Harvey 1999). Among the 24 species of Albunea, four are known only as fossils (WoRMS 2019). The diversity and distributions of most albuneids were reported by Boyko (2002, 2010).